2007
DOI: 10.1111/j.1527-5299.2007.05868.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Biventricular Pacing in Patients With Recent Myocardial Infarction: Impact on Ventricular Remodeling

Abstract: To test the hypothesis that biventricular pacing after a myocardial infarction with reduced ejection fraction can attenuate left ventricular (LV) remodeling, the authors studied 18 patients (myocardial infarction within 30–45 days, ejection fraction ≤30%, narrow QRS) randomized to biventricular therapy (biventricular therapy + defibrillator) (biventricular group) or implantable cardioverter‐defibrillator alone (control group). At 1, 6, and 12 months, there were no differences in functional or clinical paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
(36 reference statements)
2
11
0
Order By: Relevance
“…15 A study in patients 30 to 45 days after MI with reduced ejection fraction and narrow QRS suggests biventricular pacing attenuated LV dilation compared with a nonpaced group. 20 The present animal data support these findings and suggest a possible mechanism for these beneficial effects. Using regional strain and stroke work to assess regional loading characteristics, we showed that pacing preexcitation can preferentially reduce these loading characteristics.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…15 A study in patients 30 to 45 days after MI with reduced ejection fraction and narrow QRS suggests biventricular pacing attenuated LV dilation compared with a nonpaced group. 20 The present animal data support these findings and suggest a possible mechanism for these beneficial effects. Using regional strain and stroke work to assess regional loading characteristics, we showed that pacing preexcitation can preferentially reduce these loading characteristics.…”
Section: Discussionsupporting
confidence: 80%
“…Recent clinical data suggest that long-term pacing starting 30 to 60 days after MI may attenuate ventricular remodeling. 20 However, no studies exist that have assessed the mechanistic effects of preexcitation and regional unloading on short-term hemodynamics and long-term ventricular remodeling after acute MI.…”
mentioning
confidence: 99%
“…There is an emerging interest in using electrical stimulation of the myocardium as a means to attenuate and/or prevent adverse LV remodeling after MI (4,5,18). For example, in a clinically relevant porcine MI model, Shuros et al (18) demonstrated that early electrical activation of the border region attenuated the increase in LV dimensions 8 wk after MI induction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a clinically relevant porcine MI model, Shuros et al (18) demonstrated that early electrical activation of the border region attenuated the increase in LV dimensions 8 wk after MI induction. In a group of MI patients with narrow QRS complexes implanted with cardiac resynchronization devices, Chung et al (5) reported that early electrical activation of the MI border region was associated with a reduction in LV end-diastolic volumes 12 mo after the initiation of pacing.…”
Section: Discussionmentioning
confidence: 99%
“…19 In this observational pilot study of 18 patients, no deaths occurred, no patients receiving CRT-D devices deteriorated in NYHA class, and therapy patients had improved quality of life at 1 year (similar to controls). Although 1 patient had a lead dislodgement, no unanticipated adverse events were reported.…”
Section: Discussionmentioning
confidence: 99%